Desain perbaikan kualitas produksi beras menggunakan pendekatan SUR (Standardized Unitless Rating) UD. Hasil Bumi Kediri - Abdulloh, Mohamad Fauzin; Haikal, A Anas; Anbiya, Henry Hafidz (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The purpose of this study is to shadow the weighting of very important criteria to improve the quality of the production process at UD. Hasil Bumi; performance satisfaction from suppliers to improve the quality of the production process at UD. Hasil Bumi. The research methodology uses the SUR (STANDARDIZED UNITLESS RATING) method. The number of respondents for this analysis is 3 worker actors from UD. Hasil Bumi. SUR respondents are suppliers of 3 CV brands. Supplier performance using the SUR method, stated as the most superior in providing performance to UD. Hasil Bumi is CV. C under the control of Gunawan Ariawan. The value obtained from the total sub-criteria with a total SUR value of 2.04.